Resilience, alexithymia, and university stress in relation to anxiety and problematic alcohol use among female university students. (30th May 2019) - Lyvers, Michael; Holloway, Natalie; Needham, Katarina; Thorberg, Fred A.
Abstract: Objectives: University students in Australia report higher levels of stress than non‐students of the same age, with females reporting higher stress than males. The ability to successfully adapt to, and cope with, stressful situations and events, often referred to as resilience, requires social and interpersonal resources as well as the ability to effectively self‐regulate emotions. When such resources and abilities are deficient, responses to university stress are likely to be maladaptive. Deficient emotional self‐regulation is characteristic of individuals with the subclinical personality trait alexithymia, who also tend to suffer from social and interpersonal difficulties; thus students with alexithymia may be especially susceptible to university stress and associated adverse outcomes of low resilience. The present study examined resilience in relation to alexithymia, university stress, and two common outcomes of the latter in female university students: anxiety and problematic drinking. Method: Validated self‐report measures of the relevant constructs were completed online by 136 female university students from two Australian universities. All participants indicated they had English‐language proficiency and no history of serious head injury or diagnosed psychological disorder. Results: Serial mediation models indicated that resilience showed the predicted protective relationship to both problematic drinking and anxiety through lower levels of alexithymia and university stress. Conclusions: Findings suggest that students who lack resilience are more likely to report stress at university, as well as associated adverse outcomes such as anxiety and problematic drinking, due to deficiencies in emotional self‐regulation and inadequate use of social and interpersonal resources for successful coping.